The linguistic human rights plight of hungarians in Ukraine - Csernicskó István; Черничко Степан; Csernicsko Istvan; Kontra Miklós; Контра Міклош (John Wiley & Sons, Inc., 2023)
Abstract. In a review article of multilingualism in post-Soviet successor states Pavlenko (2013, p. 263) stated that a new wave of scholarship ‘is beginning to ask new questions about post-Soviet multilingualism that were not asked in previous research, focused on language reforms’. In this article we will ask two such questions: (i) Can a State restrict such language rights of a minority that the minority has traditionally enjoyed while belonging to various states in different political systems? and (ii) Can a newly independent State repeal such rights of the minorities living in its territory as had been enjoyed by the now titular nation when they themselves were a minority earlier? We pose these questions by analysing the current situation of the Hungarian minority in newly independent Ukraine.
Editorial board: https://onlinelibrary.wiley.com/doi/epdf/10.1002/9781119753926.fmatter Table of Contents: https://onlinelibrary.wiley.com/doi/book/10.1002/9781119753926
Keywords: language law; Ukraine; linguistic; hungarian